2021
DOI: 10.1007/s11626-021-00609-y
|View full text |Cite
|
Sign up to set email alerts
|

rno-miR-128-3p promotes apoptosis in rat granulosa cells (GCs) induced by norepinephrine through Wilms tumor 1 (WT1)

Abstract: The mechanism related to ovarian follicular is complex, which has not been fully elucidated. Abundant reports have confirmed that the ovarian function development is closely related to sympathetic innervation. As one of the major neurotransmitters, norepinephrine (NE) is considered an effective regulator of ovarian functions like granulosa cell (GC) apoptosis. However, the mechanism between NE and GC apoptosis in rat is still unclear. In our study, GCs were isolated and cultured in vitro with NE treatment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…In this study, miR-128-3p can inhibit the proliferation of KGN cells and promote apoptosis, which is consistent with the results reported by Ning Z. et al, who observed that miR-128-3p inhibited the proliferation and promoted the apoptosis of chicken primary GCs [ 46 ]. Furthermore, the inhibition of miR-128-3p in rats can alleviate the adrenaline-induced apoptosis of GCs [ 47 ]. These results imply that the regulatory role of miR-128-3p in the proliferation and apoptosis of follicular GCs may be evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, miR-128-3p can inhibit the proliferation of KGN cells and promote apoptosis, which is consistent with the results reported by Ning Z. et al, who observed that miR-128-3p inhibited the proliferation and promoted the apoptosis of chicken primary GCs [ 46 ]. Furthermore, the inhibition of miR-128-3p in rats can alleviate the adrenaline-induced apoptosis of GCs [ 47 ]. These results imply that the regulatory role of miR-128-3p in the proliferation and apoptosis of follicular GCs may be evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%